Target miRNA identification for the LPL gene in large yellow croaker (Larimichthys crocea) - Kalim Ullah; Aslam Hossain; Mingyue Cao; Liangyi Xue; Yajun Wang (Scientific Reports)
Abstract MicroRNA (miRNA), a conservatively evolved single-stranded non-coding RNA, exerts pivotal control over the appearance of target genes and several biological processes. This study conducted a comprehensive screening of candidate microRNAs (miRNAs) associated with Lipoprotein Lipase (LPL) in the large yellow croaker (Larimichthys crocea), utilizing sophisticated bioinformatics techniques across the species’ muscular and hepatic tissues. The bioinformatics analysis facilitated the compilation and examination of miRNA datasets specific to these tissues. The investigation culminated in the identification of miR-84a and miR-1231-5p as key miRNAs that modulate fat hydrolysis, highlighting their potential roles in lipid metabolism. Subsequent in-depth analysis further implicated these miRNAs, along with miR-891a, as prospective targets of LPL, suggesting their integral involvement in the regulation of this critical enzyme. Validation of these bioinformatics predictions was conducted through the construction of double luciferase reporters concealing the LPL 3′ untranslated region (3′UTR), substantiating that miR-84a and miR-1231-5p can modulate LPL expression via the LPL 3′UTR. Conversely, miR-891a was not concerned with this regulatory mechanism. Site-directed mutagenesis experiments elucidated the specificity of the interaction sequences. Quantitative PCR assays suggested that miR-84a and miR-1231-5p might influence LPL expression during the starvation phase, intimating the regulatory role of miRNA in fatty acid metabolism within hepatic and muscular tissue under starvation. These findings offer a nuanced understanding of LPL’s molecular functionality under stress conditions in fish, emphasizing the regulatory dynamics of miRNA during metabolic stress.